Explainable AI feature importance analysis of CTGAN-DC model for Kawasaki Disease prediction using SHapley Additive exPlanations (SHAP). - Chuan-Sheng Hung (20489202) (2024)
Explainable AI feature importance analysis of CTGAN-DC model for Kawasaki Disease prediction using SHapley Additive exPlanations (SHAP).